1975
DOI: 10.1111/j.1095-8649.1975.tb04622.x
|View full text |Cite
|
Sign up to set email alerts
|

The helminth parasites of the bullhead Cottus gobio (L.) and the stone loach Noemacheilus barbatulus (L.) from the River Avon, Hampshire

Abstract: Specimens of Cottus gobio and Noeriiarheilus barbatulus from the River Avon, Hampshire, were examined between July 1970 and July 1971. Both fish were found to act as hosts for Nicolla gallica (adult), Poinphorhynchus laevis (adult) and Triuenophorus nodulosus (plerocercoid). The incidence and intensity of infection were lower in M. barbatulus than in C. gobio, and this was related to differences in host diet. A small number of N. bavbatulus were also found to harbour Proteocephahs toridosus. Seasonal cycles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As noted by Bibby (1972), Rampus (1975), Evans (1977), Lian and Leong (1979), Moravec (1985), Zaman and Leong (1987a, b) and Wierzbicka (1991), carnivorous/omnivorous species of fishes are more prone to parasitic infections as they stand higher chances of acquiring parasites, particularly heteroxenous forms than the herbivorous forms, which because of the restriction in food, do not have the chances of acquiring more infections nor more varied fauna of parasites.…”
Section: Overall Nature Of Parasitic Infectionsmentioning
confidence: 99%
“…As noted by Bibby (1972), Rampus (1975), Evans (1977), Lian and Leong (1979), Moravec (1985), Zaman and Leong (1987a, b) and Wierzbicka (1991), carnivorous/omnivorous species of fishes are more prone to parasitic infections as they stand higher chances of acquiring parasites, particularly heteroxenous forms than the herbivorous forms, which because of the restriction in food, do not have the chances of acquiring more infections nor more varied fauna of parasites.…”
Section: Overall Nature Of Parasitic Infectionsmentioning
confidence: 99%
“…Each parasite is known to induce specific behavioural modifications in their intermediate host, with P. laevis affecting mainly phototactism, whereas P. minutus reverses geotactism (Ce ´zilly et al 2000). Pomphorhynchus laevis is known to establish in several fish species, including the bullhead (Rumpus 1975;Kennedy 1999). By contrast, being predated by a bullhead represents a dead-end for P. minutus.…”
mentioning
confidence: 99%
“…The seasonal cycles of Allocreadium isoporum and Azygia lucii have also been shown to be temperature dependent (Malakova, 1963;Dogiel, 1964;Halvorsen, 1972). Conversely Bibby (1972) in the case of Macrolecithus papilliger and Rumpus (1975) in the case of Nicolla gallica showed that the seasonal cycles and population intensity of these flukes are related to the availability of infective larvae and changes in the feeding habits and general physiological condition of the host. Recently Evans (1977) observed seasonal cycles of Sphaerostoma bramae and Asymphylodora kubanicum in the roach in Worcester-Birmingham canal and stated that they may be explained in terms of the feeding habits of the host and seasonal fluctuations in environmental temperature as well as the reproductive state of the host.…”
Section: Discussionmentioning
confidence: 99%